2010
DOI: 10.1364/oe.18.017805
|View full text |Cite
|
Sign up to set email alerts
|

Particle-swarm-optimization-assisted rate equation modeling of the two-peak emission behavior of non-stoichiometric 
CaAl_xSi_(7-3x)/4N_3:Eu^2+ phosphors

Abstract: We examined non-stoichiometric CaAl(x)Si((7-3x)/4)N(3):Eu(2+) phosphors that were intentionally prepared with x = 0.7-1.3 to identify the origin of the deconvoluted Gaussian components that constitute the emission spectra of stoichiometric CaAlSiN(3):Eu(2+) phosphors. The Al/Si molar ratio around the Eu(2+) activator caused the deconvoluted Gaussian peaks. The Eu(2+) activator sites in Al-rich environments gave rise to the lower-energy emission peak, while those in Si-rich environments were related to the high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 45 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…However, we also observed the same finding in CaAlSiN 3 :Eu 2+ phosphors and have suggested a plausible explanation-the local structure difference gave rise to the different emission peaks, and active energy transfer between them caused the varying decay rates as a function of the detection wavelength. 25,26 This interpretation could be applicable not only to CaAlSiN 3 :Eu 2+ but also to MgAlSiN 3 :Eu 2+ .…”
Section: Resultsmentioning
confidence: 84%
“…However, we also observed the same finding in CaAlSiN 3 :Eu 2+ phosphors and have suggested a plausible explanation-the local structure difference gave rise to the different emission peaks, and active energy transfer between them caused the varying decay rates as a function of the detection wavelength. 25,26 This interpretation could be applicable not only to CaAlSiN 3 :Eu 2+ but also to MgAlSiN 3 :Eu 2+ .…”
Section: Resultsmentioning
confidence: 84%
“…Moreover, the larger the valency is, the more strongly it will pull away from the charge from the activator and the ligand will be. This phenomenon explains why the emission spectrum will redshift when the Si 4+ ions are substituted by Al 3+ ions. In the current case, the redshift contribution can be attributed to the substitution of Al 3+ ions by Li + ions because Li + possesses lower charges. This effect makes Li + pull less charge away from the ligands and leads to a stronger interaction between the activator and ligands; hence, the stronger nephelauxetic effect can be expected.…”
Section: Results and Discussionmentioning
confidence: 67%
“…J. Yang et al reported the Eu 2+ doped CaAlSiN 3 fabricated by an alloy-nitridation method, and the increase of Al/Si molar ratio makes red shift of emission band [ 5 ]. Y. W. Jung reported that the higher Al/Si ratio deactivated the high-energy component and a red-shift was observed [ 6 ].…”
Section: Introductionmentioning
confidence: 99%